Analysis Protection of the Right to Freedom of Religion in Prohibition of Worship at Al Aqsa Mosque by Israeli Police to Palestinians: Insight from Indonesia - Maryoga, Yuawanda Tri; el Fasha, Ibrahimi Yahya (Faculty of Law, Universitas Negeri Semarang, 2022)
This study conducts an analysis of the protection of the right to freedom of religion amidst the prohibition of worship at the Al Aqsa Mosque by Israeli police targeting Palestinians. Amidst ongoing tensions in the region, particularly in Jerusalem, this research scrutinizes the legal frameworks and human rights implications surrounding the restrictions imposed on worship activities at one of Islam's holiest sites. Utilizing qualitative research methods, including legal analysis and examination of relevant international human rights instruments, this study aims to elucidate the complexities and challenges faced by Palestinians in exercising their religious freedoms. Through an exploration of primary and secondary data sources, including reports, legal documents, and testimonies, this research seeks to shed light on the socio-political context and legal justifications underpinning the actions of the Israeli authorities. Ultimately, this study contributes to the broader discourse on religious freedom and human rights violations in conflict-affected areas, highlighting the urgent need for international attention and intervention to safeguard the rights of Palestinians to worship freely at the Al Aqsa Mosque.